1997
DOI: 10.1017/s0890037x00042913
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phenological Stage on Detectability of Yellow Hawkweed (Hieracium pratense) and Oxeye Daisy (Chrysanthemum leucanthemum) with Remote Multispectral Digital Imagery

Abstract: Many upland pastures and forest meadows in the western United States contain significant infestations of yellow hawkweed and oxeye daisy. Documentation of infestations is necessary in order to plan and assess control tactics. Previous work with an airborne charge coupled device (CCD) with spectral filters indicated that flowering yellow hawkweed with at least 30% cover was detectable at 1 m resolution. A single image of a large area may not capture all plants in the flowering phase and multiple images are cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 9 publications
0
32
0
1
Order By: Relevance
“…Regardless of the reasons, our classification results were consistent with the literature. For example, classification accuracies were better for yellow hawkweed and oxeye daisy (Chrysanthhemum leucanthemum) in full bloom than at early and post bloom stages [77]. In addition, high mapping accuracies were achieved for the peak flowering stage of leafy spurge [60], which indicated that image classification at preflowering and post-flowering stages would have missed some areas occupied by this species because of its similar spectral characteristic with background vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the reasons, our classification results were consistent with the literature. For example, classification accuracies were better for yellow hawkweed and oxeye daisy (Chrysanthhemum leucanthemum) in full bloom than at early and post bloom stages [77]. In addition, high mapping accuracies were achieved for the peak flowering stage of leafy spurge [60], which indicated that image classification at preflowering and post-flowering stages would have missed some areas occupied by this species because of its similar spectral characteristic with background vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…It was utilized in England for treatment of running eyes, cholera, ulcers and "as an application to the secret parts" (Culpeper 1953). L. vulgare infusions are still prescribed by herbalists for treatment of asthma, whooping-cough and nervous excitability, and lotions are recommended for ulcers and sores (le Strange 1977).…”
Section: Economic Importancementioning
confidence: 99%
“…Similarly, yellow starthistle (Centaurea solstitialis), tamarisk (Tamarix spp. ), yellow hawkweed (Hieracium pratense), oxeye daisy (Chrysanthemum leucanthemum), and Chinese tallow (Sapium sebiferum) also have distinctive colorations that can facilitate remote sensing [22][23][24]. Other species have been detected by their extended growing periods.…”
Section: Introductionmentioning
confidence: 99%